(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Although climate change is a worldwide phenomenon, individuals with disabilities are affected in a peculiar way, with noticeable repercussions in terms of the effectiveness of their rights. The essay has two goals. The first is to explore, through the adoption of an interdisciplinary approach, the impact of climate change on the right to health of persons with disabilities. The second is to investigate, starting from the recent constitutional reform on the environment, normative and interpretative perspectives with which it is possible to guarantee the effectiveness of this right in the context of the design of fair and inclusive policies against the phenomenon.